Enhancing Reading Comprehension Skills in ESL Learners through Read-Aloud Strategies: A Quasi-Experimental Study - Shoukat, Shaharyar; Usman, Zarmina; Faheem, Hafiz Muhammad (Journal of Development and Social Sciences, 2024)
This research examines the effects of the read-aloud strategy on improving reading comprehension of Grade 2 ESL learners in Lahore, Pakistan. Reading comprehension is a significant aspect of academic achievement, yet Pakistani primary students suffer because of limited proficiency in English and traditional rote-based methods of teaching. A quasi-experimental design was utilized with 50 students placed into an experimental group who received interactive read-aloud sessions, and a control group utilizing traditional methods. Literacy, inferential, and evaluative levels of comprehension are measured using pre- and post-tests. Results reflect significant comprehension gain in the experimental group with large effect sizes for all stories. The study shows the read-aloud technique to be effective. Recommendations are that read-aloud sessions must be included in the ESL curriculum and that teachers are trained in expressive reading and interactive questioning. Read-aloud methods can help build critical thinking, engagement, and literacy in ESL settings.